2009
DOI: 10.1007/s11431-009-0255-5
|View full text |Cite
|
Sign up to set email alerts
|

Improved GaN grown on Si(111) substrate using ammonia flow modulation on SiN x mask layer by MOCVD

Abstract: In this paper, 1 μm n-GaN was grown by using varied and fixed ammonia flow (NH 3 ) on SiN x mask layer on Si(111) substrate using metal organic chemical vapor deposition (MOCVD). In-situ optical reflectivity traces of GaN growth show that the three-to two-dimensional process has been prolonged by using varied ammonia flow on SiN x mask layer method compared with that grown by fixing ammonia flow. Structural and optical properties were characterized by high-resolution X-ray diffraction and photoluminescence, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
(7 reference statements)
2
6
0
Order By: Relevance
“…Introducing SiN as a masking layer just before growing HT‐GaN thick film leads to decrease in the reflectance intensity. The decrease is attributed to a rough surface and aforementioned initial 3D growth mode of GaN from nucleus islands leading to subsequent lateral overgrowth of GaN until full coalescence is achieved, which was also observed by several research groups and author himself . It was found that variation in V/III ratio during final GaN layer growth strongly influences heterostructure morphology, its roughness and degree of characteristic micropits creation .…”
Section: Resultssupporting
confidence: 54%
“…Introducing SiN as a masking layer just before growing HT‐GaN thick film leads to decrease in the reflectance intensity. The decrease is attributed to a rough surface and aforementioned initial 3D growth mode of GaN from nucleus islands leading to subsequent lateral overgrowth of GaN until full coalescence is achieved, which was also observed by several research groups and author himself . It was found that variation in V/III ratio during final GaN layer growth strongly influences heterostructure morphology, its roughness and degree of characteristic micropits creation .…”
Section: Resultssupporting
confidence: 54%
“…Prior to the growth, the substrates were heated up to 1190 • C for 10 minutes in an H 2 atmosphere to remove the native oxide. Then, a 40 nm-thick AlN nucleation layer was deposited at 1150 • C, followed by a SiN x mask layer growth at 1160 • C [12] . This SiN x mask did not cover the AlN surface completely.…”
Section: Methodsmentioning
confidence: 99%
“…An HT-AlN (HT for "High-Temperature") nucleation layer was grown on the Si substrate at the same temperature, followed by the deposition of a SiN x in situ mask for 110 seconds. 1 µm undoped-GaN buffer layer was then grown using an ammonia flow modulation method [10]. An 8-pair superlattice consisted of 6 nm HT-AlN/25nm HT-AlGaN was inserted to reduce the tensile stress.…”
Section: Methodsmentioning
confidence: 99%